2009
DOI: 10.1213/ane.0b013e3181a2a301
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Ropivacaine Concentrations for Intraoperative Analgesia During Major Upper Abdominal Surgery: A Prospective, Randomized, Double-Blinded, Placebo-Controlled Study

Abstract: Epidural administration of 0.5% ropivacaine leads to a more pronounced sparing effect on desflurane concentration for an adequate anesthetic depth when compared with a 0.2% concentration of ropivacaine at comparable levels of vasopressor support and i.v. fluid requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
0
17
0
3
Order By: Relevance
“…To facilitate comparisons between the three groups, we used the same volume of ropivacaine for each group and noted that lower concentrations resulted in significant dose reduction without compromising efficacy. Panousis et al compared ropivacaine 0.2% and 0.5% for epidural anaesthesia combined with general anaesthesia and did not observe a significant difference in the need for vasopressors or intravenous fluid 15 . In contrast to our findings, they found that ropivacaine 0.2% did not consistently provide adequate intraoperative analgesia, such that more remifentanil was used for rescue analgesia, thereby inducing hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate comparisons between the three groups, we used the same volume of ropivacaine for each group and noted that lower concentrations resulted in significant dose reduction without compromising efficacy. Panousis et al compared ropivacaine 0.2% and 0.5% for epidural anaesthesia combined with general anaesthesia and did not observe a significant difference in the need for vasopressors or intravenous fluid 15 . In contrast to our findings, they found that ropivacaine 0.2% did not consistently provide adequate intraoperative analgesia, such that more remifentanil was used for rescue analgesia, thereby inducing hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Panousis et al evaluated the effect of different epidurally administered concentrations of ropivacaine on inhaled anesthetic, fluid and vasopressor requirement and hemodynamic changes. They concluded that ropivacaine 0.5% compared with a ropivacaine 0.2 % concentration led to a greater inhaled anesthetic-sparing effect at t h e s a m e l e v e l s o f I V f u i d s u p p l y a n d vasopressor support (Panousis et al, 2009). In a critical appraisal published on 2008, Pratt WB et al concluded that although it may provide more effective initial pain control, epidural analgesia does not necessarily improve the critical outcome as after pancreatoduodenectomy.…”
Section: Epidural Anaesthesia / Analgesiamentioning
confidence: 99%
“…U našem ispitivanju primarni cilj bio je poređenje efekata epiduralne primene niže i više koncentracije bupivakaina na intraoperativnu potrošnju sevoflurana. Imajući u vidu da su prosečna vrednost i vrednost promena Fi sevo bile značajno više i veće u grupi 1 nego u grupi 2 uz prisustvo sličnih vrednosti SAP i SF tokom operacije među grupama, kao i analizom rezultata drugih autora i njihovih zaključaka, dolazi se do saznanja da dubina opšte anestezije mnogo više varira ukoliko se ona izvodi u kombinaciji sa nižom koncentracijom epiduralnog LA [3,8,12]. Imajući u vidu da su prosečna vrednost i vrednost promena Fi sevo bile značajno više i veće u grupi 1 nego u grupi 2 uz prisustvo sličnih vrednosti SAP i SF tokom operacije među grupama, kao i analizom rezultata drugih autora i njihovih zaključaka, dolazi se do saznanja da dubina opšte anestezije mnogo više varira ukoliko se ona izvodi u kombinaciji sa nižom koncentracijom epiduralnog LA [3,8,12].…”
Section: Diskusijaunclassified
“…Ti nalazi su u saglasnosti sa rezultatima dosadašnjih ispitivanja [12,17]. Ti nalazi su u saglasnosti sa rezultatima dosadašnjih ispitivanja [12,17].…”
Section: Tabela 2intraoperativno Primenjeni Lekovi I Anesteticiunclassified
See 1 more Smart Citation